INTEGRATING AI AND ENGLISH EDUCATION INTO UZBEKISTAN’S CULTURAL DIPLOMACY FRAMEWORK - Rustamov Alijon Amonkulovich (TADQIQOTLAR, 2026)
Abstract: This article examines the strategic integration of artificial intelligence and English language pedagogy into the cultural diplomacy framework of the Republic of Uzbekistan. In the era of rapid digital globalization and structural domestic reforms, foreign language proficiency serves as a critical conduit for soft power projection, international academic integration, and economic diplomacy. This study evaluates how the systematic implementation of AI-driven educational technologies-such as intelligent tutoring platforms, automated neural translation models, and adaptive linguistic analytics-can optimize Uzbekistan’s public diplomacy initiatives. Through a systematic analysis of current educational policies and digital infrastructure developments, the research establishes an actionable conceptual framework for utilizing automated language training to cultivate a globally competitive workforce while projecting a modern, technologically progressive national narrative. The paper concludes with policy recommendations designed to align algorithmic language acquisition with the state’s strategic foreign policy objectives.